Efektivitas Pelayanan Program Kartu Identitas Anak (Kia) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ponorogo - Syamsudin, Nurul Aulia; Prastyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The Child Identity Card (KIA) Program service is one of the population programs for children aged 0-17 years that has been implemented since 2018 at the Population and Civil Registration Office of Ponorogo Regency. The difficulty of the community in taking care of making KIA and the lack of understanding of the use of KIA is still a challenge for Dispendukcapil employees. This study aims to describe and analyze the results of the effectiveness of the KIA Program services at the Dispendukcapil of Ponorogo Regency. The research method used is descriptive qualitative. The theory of effectiveness used is Duncann's theory, namely Goal Achievement, Integration, and Adaptation which includes seven sub-indicators, namely timeframe, objectives, legal basis, socialization process, procedures, capacity building, and facilities and infrastructure. The results of the study found that of the seven sub-indicators had been carried out well although there were still two sub-indicators that were still less than optimal. KIA program services have been carried out in accordance with the working hours of Dispendukcapil employees; the legal basis used is in accordance with Permendagri No. 2 of 2016; targets are given to children aged 0-17 years; socialization is carried out by cooperation agreements and going directly to the field using operational vehicles even though it is not yet comprehensive; procedures provided are in accordance with regulations; the ability of qualified and competent employees even though there are still a few employees; and adequate facilities and infrastructure.